Model Checking Software 16th International SPIN Workshop, Grenoble, France, June 26-28, 2009, Proceedings - Pasareanu, Corina S. (Theoretical Computer Science and General Issues, 2009)
This book constitutes the refereed proceedings of the 16th International SPIN workshop on Model Checking Software, SPIN 2009, held in Grenoble, France, in June 2009. The 15 revised full papers presented together with 3 tool papers and 4 invited talks were carefully reviewed and selected from 41 submissions. The papers cover theoretical and algorithmic foundations as well as tools for software model checking by addressing theoretical advances and empirical evaluations related to state-space and path exploration techniques, as implemented in software verification tools.